PENGARUH MOTIVASI DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI PADA KEMENTERIAN AGAMA DI KABUPATEN LEBAK - Eris Harismasakti; Abdul Mujib (Universitas La Tansa Mashiro, 2024)
To find out the influence of motivation on employee performance in employees at the Lebak Regency Ministry of Religion Office. To find out the effect of work facilities on employee performance in the Lebak Regency Ministry of Religion Office employees. To find out simultaneously the influence of motivation and work facilities on employee performance in Lebak Regency Ministry of Religion Office employees. This research used a sampling technique, namely Sampling/Saturated Sample